2006
DOI: 10.2166/wqrj.2006.043
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of PAA Demand and its Implications on Disinfection of Wastewaters

Abstract: Disinfectant demand and microbial inactivation rate are essential issues for assessing disinfection performance and proper design of disinfecting systems. In the United Kingdom and Italy, peracetic acid (PAA) has recently become an accepted disinfectant for treating wastewaters prior to reuse in agriculture, and its use is likely to spread worldwide due to its efficacy as well as the benign nature of the by-products produced. In this paper, overall PAA demand during the advanced disinfection of municipal waste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 33 publications
(36 reference statements)
3
50
0
5
Order By: Relevance
“…Two organic peroxides, peracetic acid (PAA) and performic acid (PFA), which fulfil the disinfectant requirements given by Tchobanoglous et al (2003) have emerged as alternatives to the chlorine compounds for disinfection of wastewater treatment plant (WWTP) effluents. PAA is a strong disinfectant with a wide spectrum of antimicrobial activity that was introduced to wastewater treatment around 15 years ago (Antonelli et al, 2006;Falsanisi et al, 2006;Kitis, 2004;Koivunen and Heinonen-Tanski, 2005). Commercially available PAA, is available as an acidic quaternary equilibrium mixture of peracetic acid (PAA), hydrogen peroxide, acetic acid, and water:…”
Section: Highlightsmentioning
confidence: 99%
“…Two organic peroxides, peracetic acid (PAA) and performic acid (PFA), which fulfil the disinfectant requirements given by Tchobanoglous et al (2003) have emerged as alternatives to the chlorine compounds for disinfection of wastewater treatment plant (WWTP) effluents. PAA is a strong disinfectant with a wide spectrum of antimicrobial activity that was introduced to wastewater treatment around 15 years ago (Antonelli et al, 2006;Falsanisi et al, 2006;Kitis, 2004;Koivunen and Heinonen-Tanski, 2005). Commercially available PAA, is available as an acidic quaternary equilibrium mixture of peracetic acid (PAA), hydrogen peroxide, acetic acid, and water:…”
Section: Highlightsmentioning
confidence: 99%
“…The disinfection efficiency of PAA in wastewater applications has been demonstrated numerous times in the literature (Antonelli et al, 2006;Baldry, 1983;Baldry and French, 1989;Baldry et al, 1991;Baldry et al, 1995;Briancesco et al, 2005;Collivignarelli et al, 2000;Dell'Erba et al, 2004;Gehr et al, 2003;Kitis, 2004;Koivunen and Heinonen-Tanski, 2005a;Koivunen and Heinonen-Tanski, 2005b;Lefevre et al, 1992;Liberti and Notarnicola, 1999;Liberti et al, 1999;Salgot et al, 2002;Veschetti et al, 2003;Zanetti et al, 2007). As a result, PAA is gaining acceptance as a disinfectant, especially in the United Kingdom and Italy (Falsanisi et al, 2006 A recent study by Azzellino et al (2011) showed that PAA disinfection is more dependent on dosage than on contact time. This indicates that the traditional C•t (dose amount x contact time) concept may need a weighting coefficient for the t term.…”
Section: Introductionmentioning
confidence: 97%
“…First order degradation kinetics did not fit the observed data, due to the considerable initial consumption of oxidants. To address the initial consumption of PAA, a modified first order kinetics expression was applied (Antonelli et al, 2006;Chhetri et al, 2016;Falsanisi et al, 2006) to model the concentration profile of PAA in wastewater effluents, including a parameter describing initial oxidant consumption as described by Haas and Finch (Haas and Finch, 2001): Rapid degradation of PAA was observed in the wastewater pretreated by PAX XL 100 and almost all PAA was degraded within 60 min except for the highest dose of 12 mg/L PAA. We previously observed rapid degradation of PAA in combined sewer overflow, however, only when it was not pretreated with PAX XL 100 (Chhetri et al, 2016).…”
Section: Concentration Profile Of Paamentioning
confidence: 99%
“…Ozone is a very efficient disinfectant; however, the sophisticated technology to generate ozone makes it unsuitable for disinfection of wastewater in the Arctic region. Organic peroxide, peracetic acid (PAA) is a strong disinfectant with a wide spectrum of antimicrobial activity, which was introduced to wastewater treatment approximately 30 years ago (Antonelli et al, 2006;Baldry, 1983;Falsanisi et al, 2006;Kitis, 2004;Koivunen and Heinonen-Tanski, 2005;Luukkonen et al, 2015) and recently it has been used to disinfect combined sewer overflows (Chhetri et al, 2016(Chhetri et al, , 2014. Commercial PAA is available as an acidic quaternary equilibrium mixture of PAA, hydrogen peroxide, acetic acid, and water:…”
Section: Introductionmentioning
confidence: 99%